Analysis of data collected in the European Society for Blood and Marrow Transplantation (EBMT) registry on a cohort of lymphoma patients receiving plerixafor - Sureda, Anna; Dreger, Peter (Bone marrow transplantation, 2020)
Plerixafor + granulocyte-colony stimulating factor (G-CSF) is administered to patients with lymphoma who are poor mobilizers of hematopoietic stem cells (HSCs) in Europe. This international, multicenter, non-interventional registry study (NCT01362972) evaluated long-term follow-up of patients with lymphoma who received plerixafor for HSC mobilization versus other mobilization methods. Propensity score matching was conducted to balance baseline characteristics between comparison groups. The following mobilization regimens were compared: G-CSF + plerixafor (G + P) versus G-CSF alone; G + P versus G-CSF + chemotherapy (G + C); and G-CSF + plerixafor + chemotherapy (G + P + C) versus G + C. The primary outcomes were progression-free survival (PFS), overall survival (OS), and cumulative incidence of relapse (CIR). Overall, 313/3749 (8.3%) eligible patients were mobilized with plerixafor-containing regimens. After propensity score matching, 70 versus 36 patients were matched in the G + P versus G-CSF alone cohort, 124 versus 124 in the G + P versus G + C cohort, and 130 versus 130 in the G + P + C versus G + C cohort. For both PFS and OS, the upper bound of confidence interval for the hazard ratio was >1.3 for all comparisons, implying that non-inferiority was not demonstrated. No major differences in PFS, OS, and CIR were observed between the plerixafor and comparison groups.